2005
DOI: 10.1016/j.cellbi.2004.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the GLUT1 and GLUT9 facilitative glucose transporters in embryonic chondroblasts and mature chondrocytes in ovine articular cartilage

Abstract: Glucose transport across the chondrocyte membrane is essential for chondrogenesis and the development of the skeletal system. We have previously used RT-PCR to show that fully developed human articular chondrocytes express transcripts for the GLUT1 and GLUT9 glucose transporters. In this study we report on the expression and immunohistochemical localization of the GLUT1 and GLUT9 proteins in embryonic and mature ovine cartilage. We also provide Western blot evidence for GLUT1 and GLUT9 expression in mature ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The close relationship between energy metabolism and skeletal growth is supported by the well-established growthregulatory role of insulin during early postnatal life (20,65) as well as chondrogenesis in prenatal life and in postnatal development of articular cartilage (32). However, the definite relationship between energy controlling mechanisms and growth in skeletal tissues still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship between energy metabolism and skeletal growth is supported by the well-established growthregulatory role of insulin during early postnatal life (20,65) as well as chondrogenesis in prenatal life and in postnatal development of articular cartilage (32). However, the definite relationship between energy controlling mechanisms and growth in skeletal tissues still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Human GLUT9a has 540 amino acids and is encoded by 12 exons, whereas GLUT9b is 512 amino acids long and encoded by 13 exons, spread over an approximately 250-kb genomic region. In both humans and mice, GLUT9b expression is restricted to liver and kidney, whereas GLUT9a has a broad tissue distribution including liver, kidney, intestine, leukocytes, and chondrocytes (85), where its expression is upregulated by inflammatory cytokines (86) (Figure 4). In polarized epithelial cells, human GLUT9a is expressed in the basolateral membrane, whereas GLUT9b is targeted to the apical pole (84), and in human kidney, GLUT9 is present in the proximal tubule (84).…”
Section: Other Genes Identified By Genetic Association Studiesmentioning
confidence: 99%
“…We have previously confirmed that this GLUT1 antibody recognizes GLUT1 across a diverse number of mammalian species including rats, humans, dogs, sheep, and horses. 23,24 In this study we used this GLUT1 antibody in Western blots of equine chondrocyte lysates to confirm positive immunoreactivity with a band migrating at 45-50 kDa (the expected molecular weight for GLUT1 25 ) (data not shown).…”
Section: Reagentsmentioning
confidence: 99%